First evidence of microplastic ingestion by fishes from the Amazon River estuary. (August 2018) - Pegado, Tamyris de Souza e Silva; Schmid, Kurt; Winemiller, Kirk O.; Chelazzi, David; Cincinelli, Alessandra; Dei, Luigi; Giarrizzo, Tommaso
Abstract: This study investigated occurrence of microplastic particles in digestive tracts of fishes from the Amazon River estuary. A total of 189 fish specimens representing 46 species from 22 families was sampled from bycatch of the shrimp fishery. Microplastic particles removed from fish gastrointestinal tracts were identified using Attenuated Total Reflectance – Fourier Transform Infrared (ATR-FTIR). In total, 228 microplastic particles were removed from gastrointestinal tracts of 26 specimens representing 14 species (30% of those examined). Microplastic particles were categorized as pellets (97.4%), sheets (1.3%), fragments (0.4%) and threads (0.9%), with size ranging from 0.38 to 4.16 mm. There was a positive correlation between fish standard length and number of particles found in gastrointestinal tracts. The main polymers identified by ATR-FTIR were polyamide, rayon and polyethylene. These findings provide the first evidence of microplastic contamination of biota from the Amazon estuary and northern coast of Brazil. Highlights: Microplastics occurred in 13.7% of 14 fish species from the Amazon River estuary. Pellets represented 97.4% of microplastics ingested. Polyamide, rayon and polyethylene were the main polymers identified by ATR-FTIR. Microplastic ingestion was positively correlated with fish body size.